Positive electrode composite current collector

By forming a carbonized layer containing activated carbon particles on the surface of the carbon-based conductive support layer, the problem of insufficient bonding force between the conductive layer and the substrate layer is solved, and the firm adhesion of the conductive layer and the high conductivity and thermal conductivity of the current collector are achieved.

CN119650708APending Publication Date: 2025-03-18HUAZHONG UNIV OF SCI & TECH
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411977428.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The bonding force between the conductive layer and the base layer in the existing positive electrode composite liquid collector is insufficient, resulting in poor adhesion of the conductive layer and easy delamination.

Method used

A carbonized layer is formed on the surface of the carbon-based conductive support layer. The carbonized layer contains activated carbon particles. The activated carbon particles and the conductive layer particles form a reinforcement layer at the contact interface. The conductive layer particles are deposited on the surface of the reinforcement layer to thicken to form a conductive layer.

Benefits of technology

By increasing the bonding force between the carbon-based conductive support layer and the conductive layer, the problem of delamination of the conductive layer is avoided, the conductive and thermal conductivity of the current collector is improved, and its heat resistance is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650708A_ABST
    Figure CN119650708A_ABST
Patent Text Reader

Abstract

The invention belongs to the related technical field of current collectors, and discloses a positive electrode composite current collector which comprises a carbon-based conductive supporting layer 1, a carbonization layer 2 is formed on at least one surface of the carbon-based conductive supporting layer 1, activated carbon particles are arranged in the carbonization layer 2, and an enhancement layer 21 is formed on a contact interface of the activated carbon particles and evaporated conductive layer particles. And conductive layer particles are deposited and thickened on the surface of the enhancement layer 21 to form a conductive layer 3. Based on the graphite-based matrix material, the carbonization layer is formed on the surface of the carbon-based conductive supporting layer, so that the metal layer can be attached to form the enhancement layer in the high-temperature plating process, and the adhesive force of the subsequent conductive layer is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field related to current collectors, and more specifically, relates to a positive electrode composite current collector. Background Art

[0002] In secondary batteries, current collectors are needed as the part where current converges. The material is generally aluminum foil or copper foil. Traditional metal foils are used as current collectors, which lack safety performance, and metal materials have high density and are relatively heavier. In the prior art, for safety reasons, a positive electrode composite current collector is proposed, which includes a polymer support layer and a metal layer arranged on both sides of the support layer. Compared with metal foils, it is safer and lighter, and therefore has a lower energy density.

[0003] Considering that the high rate charge and discharge of the secondary battery during use will bring about the rise of the battery temperature, the substrate in the positive electrode composite current collector is generally set to a high molecular polymer, which has poor thermal conductivity (low thermal conductivity), and the metal conductive layer is generally thin, and its lateral thermal conductivity is poor. In the patent documents CN 218525607U and CN111455323 A, a graphite film is used as a substrate, and a metal layer is formed thereon to improve conductivity and processability, and it is not easy to cause perforation due to evaporation. The graphite substrate has a certain roughness on the surface, and its surface can provide vacancies for metal bonding and anchoring during plating and deposition. For polymer substrates, the molecules on the surface will undergo a process of recrystallization and deformation under the high temperature of vapor deposition. This process will provide more anchoring vacancies for the metal particles on the vapor deposition, which is beneficial to the bonding between the metal layer and the polymer layer. However, due to the high temperature resistance of graphite itself, during the high-temperature plating process, the graphite base layer basically maintains a stable morphology, and the metal particles on the vapor deposition are only anchored to the graphite layer molecules by the intermolecular bonding force. Therefore, there is a certain degree of deficiency in the bonding force. At the same time, the graphite layer has been subjected to high-pressure extrusion treatment, and the surface is smooth and dense, which is not conducive to the physical bonding between the metal particles and the graphite layer. Summary of the invention

[0004] In view of the above defects or improvement needs of the prior art, the present invention provides a positive electrode composite current collector, thereby solving the technical problem of improving the insufficient bonding force between the conductive layer and the substrate layer.

[0005] To achieve the above-mentioned purpose, according to one aspect of the present invention, there is provided a positive electrode composite current collector, comprising a carbon-based conductive support layer 1, a carbonized layer 2 is formed on at least one surface of the carbon-based conductive support layer 1, the carbonized layer 2 contains activated carbon particles, and the activated carbon particles form a reinforcement layer 21 at the contact interface with the evaporated conductive layer particles, and the conductive layer particles are deposited and thickened on the surface of the reinforcement layer 21 to form a conductive layer 3.

[0006] Based on the above technical solution, a carbonized layer having activated carbon particles is formed on the substrate layer, which can increase the bonding force with the conductive layer and avoid the risk of subsequent delamination.

[0007] Preferably, the carbon-based conductive support layer 1 is graphite, graphene or a mixture thereof.

[0008] Based on the above technical solution, the substrate layer can have good thermal and electrical conductivity, and at the same time, excellent heat resistance, which can ensure that the composite current collector prepared subsequently is basically free of pinholes.

[0009] Preferably, the carbon-based conductive support layer 1 has a thickness of 4-50 μm.

[0010] Based on the above technical solution, the thickness of the carbon-based conductive support layer 1 can be controlled while ensuring processability to meet the needs of different scenarios.

[0011] Preferably, the carbonized layer 2 is formed by carbonizing a polymer film layer; the thickness of the carbonized layer 2 is 0.1-5 μm.

[0012] Based on the above technical solution, it is easy to prepare a carbonized layer 2 of suitable thickness, which is beneficial to processing and forming an anchoring effect, and will not affect the electrical and thermal conductivity and the thickness of the overall film.

[0013] Preferably, the polymer film layer is formed by a lamination or coating process.

[0014] Based on the above technical solution, a coating process is used to facilitate the formation of a polymer film layer on the surface of the carbon-based support layer 1. The polymer film layer formed by the coating process can be fully dispersed in the pores on the surface of the carbon-based conductive support layer 1 after coating to increase the anchoring effect, and can also increase the contact with the carbon particles in the carbon-based conductive support layer 1 during the subsequent carbonization process, participate in the formation of a hybrid structure with the carbon in the graphite, and further reduce the grain boundary defects between the carbonized layer 2 and the carbon-based conductive support layer 1.

[0015] Preferably, the carbonization formation temperature of the carbonized layer 2 is 800-1500° C., and the insulation time is 1-4 hours.

[0016] Based on the above technical solution, a relatively more active carbon structure can be formed, which is conducive to chemical reaction with the conductive layer 3 at low temperature, ensuring the stability of the reinforcement layer to form a stronger bonding force.

[0017] Preferably, the carbonization formation temperature of the carbonized layer 2 is 1000-1500°C.

[0018] Based on the above technical solution, a higher carbonization temperature can promote the graphitization of carbon, further improve the electrical and thermal conductivity, and can also reduce the defects at the interface with the carbon-based conductive support layer 1 to a certain extent, thereby increasing the bonding force between the carbonized layer 2 and the carbon-based conductive support layer 1.

[0019] Preferably, the conductive layer 3 is made of aluminum, and the reaction temperature of the contact interface is 1000-1300°C.

[0020] Based on the above technical solution, the reinforcement layer 21 can be quickly formed during the aluminum plating process without significantly changing the aluminum plating process.

[0021] Preferably, during plating, the surface temperature of the carbide layer 2 is 700-900°C, and the temperature of the evaporated aluminum vapor is 1100-1300°C.

[0022] Based on the above technical solution, the temperature difference between the two is controlled to avoid the decomposition of aluminum carbide caused by the exothermic reaction. The evaporated aluminum will not only be physically anchored with the carbide layer, but also form an appropriate amount of aluminum carbide, forming a stable chemical bond between the two.

[0023] In general, compared with the prior art, the above technical solution conceived by the present invention provides a positive electrode composite current collector having the following beneficial effects:

[0024] 1. A positive electrode composite current collector proposed in the present invention is based on a graphite-based matrix material, and a carbonized layer is formed on the surface of the carbon-based conductive support layer, which is beneficial to the adhesion of the metal layer during the high-temperature plating process to form an enhanced layer to increase the adhesion of the subsequent conductive layer.

[0025] 2. The carbon-based conductive support layer provided in the present invention is made of graphite, graphene or a mixed material thereof. Its high temperature resistance enables it to withstand a longer evaporation process and a faster evaporation rate, and deposit a thicker metal layer under the same conditions. At the same time, graphite itself provides conductivity, which improves the electron transmission capacity of the composite current collector. The carbonized layer provided in the present invention is conducive to processing and forming an anchoring effect, and does not affect the electrical and thermal conductivity and the thickness of the overall film.

[0026] 3. The present invention can facilitate the formation of a polymer film layer on the surface of the carbon-based support layer through a coating process. The polymer film layer formed through a coating process can be fully dispersed in the pores on the surface of the carbon-based conductive support layer after coating, thereby increasing the anchoring effect, and can also increase the contact with the carbon particles in the carbon-based conductive support layer during the subsequent carbonization process, participate in the formation of a hybrid structure with the carbon in the graphite, and further reduce the grain boundary defects between the carbonized layer and the carbon-based conductive support layer.

[0027] 4. In the present invention, the evaporated aluminum vapor contacts the particles on the surface of the carbide layer and is easy to react at high temperature to produce a compound reinforcement layer. The formed aluminum carbide can be embedded in the crystals of the formed carbide layer, thereby increasing the bonding force at the interface. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 2. It is a schematic diagram of the current collector structure in which a single-layer conductive layer is arranged;

[0029] Figure 2 1. It is a schematic diagram of the current collector structure with a double-layer conductive layer;

[0030] Throughout the drawings, the same reference numerals are used to denote the same elements or structures, wherein:

[0031] 1-carbon-based conductive support layer; 2-carbonized layer; 21-carbide reinforcement layer; 3-conductive layer. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0033] In some embodiments of the present application, refer to Figure 1 A positive electrode composite current collector includes a carbon-based conductive support layer 1, a carbonized layer 2 is formed on at least one surface of the carbon-based conductive support layer 1, the carbonized layer 2 contains activated carbon particles, the activated carbon particles form a reinforcement layer 21 at the contact interface with the conductive layer particles, and the conductive layer particles are deposited and thickened on the surface of the reinforcement layer 21 to form a conductive layer 3.

[0034] Specifically, in some embodiments of the present application, the carbon-based conductive support layer 1 is made of graphite, with a thickness of 4-50 μm, and has good electrical and thermal conductivity. Furthermore, the carbon-based conductive support layer 1 can also be set to graphene, and / or a mixed film layer of graphite and graphene.

[0035] Regarding the formation of the carbonized layer 2, it can be formed by high-temperature carbonization of a polymer film layer; the obtained carbonized layer has relatively high chemical activity and has higher reactivity than the carbon structure in graphite, and can react with the material in the conductive layer 3 at a lower temperature to form a stable reinforcement layer 21, thereby ensuring the stability of the reinforcement layer 21 during the preparation process, thereby facilitating increasing the adhesion of the metal layer.

[0036] In some embodiments of the present application, the carbonized layer 2 is formed by (hot rolling) laminating a PI film (polyimide film) on a carbon-based conductive support layer 1, gradually heating in a carbonization device (such as a high-temperature carbonization furnace) (heating rate of 5-10°C / s), and heating to 800-1500°C under a protective atmosphere / negative pressure, carbonizing for 1-4 hours, and applying roller pressure (such as 5-20MPa, not specifically limited) on the surface of the film after carbonization to compact the carbonized layer 2; the carbonization temperature is preferably carried out at 1000-1500°C. Of course, in the prior art, other polymer films can also be carbonized at high temperatures.

[0037] When a relatively high carbonization temperature is applied, a small amount of graphitized crystal structure will be formed, which can increase the electrical and thermal conductivity of the carbonized layer 2 and reduce the defects in the formed interface (because the carbon in the carbonized layer has a graphitized structure, it can form a coherent / semi-coherent phase boundary with the carbon-based conductive support layer of graphite material).

[0038] In some other embodiments of the present application, a PI film is formed on the surface of the carbon-based conductive support layer 1 by a coating method, and the polyimide resin is dissolved in a solvent and dispersed. The solvent can be selected from DMSO (dimethyl sulfoxide), NMP (N-methylpyrrolidone), DMF (N, N-dimethylacetamide), etc.; combined with the actual coating conditions, the mass concentration of the resin in the coating liquid is controlled to be 15%-35%, and the viscosity is 1500-3000cps (can be doped with thickeners, stabilizers, etc.) for coating, and dried after coating (hot air drying temperature is 40-80°C, drying 0.5-2h). Based on the method of forming a PI film by coating, it can be fully dispersed in the pores on the surface of the carbon-based conductive support layer 1 after coating to increase the anchoring effect. It can also increase the contact with the carbon particles in the graphite layer during the subsequent carbonization process, and participate in the formation of a hybrid structure with the carbon in the graphite to further reduce the grain boundary defects of the carbonized layer 2 and the carbon-based conductive support layer 1.

[0039] In the present application, the thickness of the formed carbonized layer 2 is preferably 0.1-5 μm. If it is too thin, it is not suitable for processing and the anchoring effect with the carbon-based conductive support layer 1 is poor. If it is too thick, it will affect the electrical and thermal conductivity, and increase the thickness of the overall film, affecting the volume density of the subsequent battery.

[0040] During the formation of the reinforcement layer 21, the interface temperature of the carbonized layer 2 and the conductive layer 3 particles in contact is set within the temperature range of the activated carbon particles and the conductive layer particles, i.e., within the range of 1000-1300°C. The reaction speed in this temperature range is relatively fast, and the formed aluminum carbide is not easy to decompose;

[0041] Among them, for commonly used current collector materials, such as aluminum as a conductive layer, aluminum is evaporated and plated; the carbon particles in the carbonized layer 2 form a reinforcement layer 21 at the contact interface at a first temperature and the conductive layer particles at a second temperature; in a vacuum environment, the vacuum degree is ensured to be above 10-2Pa, the first temperature is the temperature of the surface of the carbonized layer 2, preferably 500-800°C, at this time, the carbonized layer 2 can be heated by irradiation with an electric heating wire, and the film is kept at a relatively low speed (such as 1-2m / s); the carbonized layer on the surface under vacuum is relatively stable and not easy to oxidize, and the temperature of the evaporated aluminum vapor is controlled, that is, the second temperature is 1100-1300°C;

[0042] Aluminum vapor contacts the activated carbon particles on the surface of the carbide layer 2, and reacts easily to produce compounds at high temperature. The formed aluminum carbide can be embedded into the crystals of the formed carbide layer, thereby increasing the bonding force at the interface. The formed compound enhancement layer is conducive to the further deposition of aluminum vapor in the subsequent conductive layer.

[0043] Since the first temperature and the second temperature are lower than the decomposition temperature of aluminum carbide, and the first temperature is lower than the decomposition temperature, even if the reaction is exothermic, the temperature will not rise significantly due to the exothermic reaction and exceed the decomposition temperature of aluminum carbide, and a cooling system (such as a cooling roller) can be provided in the subsequent winding and transmission process to cool the reinforcement layer 21 formed by the plating. In some embodiments of the present application, the evaporation plating process of aluminum is combined with a suitable wire feeding amount, evaporation power (voltage, current), and the speed of the film transmission is controlled to form a reinforcement layer of suitable thickness.

[0044] Through the high-temperature evaporation plating process, combined with the formed carbonized layer 2, the adhesion between the conductive layer 3 and the substrate can be increased on the basis of the original process and equipment, while ensuring the overall thermal conductivity and electrical conductivity of the collector, especially improving the defect of poor adhesion between the graphite surface and the conductive layer.

[0045] In some other embodiments of the present application, Figure 2 As shown, the diagram illustrates the situation where the conductive layer 3 is provided on both sides. At this time, the carbonized layer 2 is formed on both surfaces of the carbon-based conductive support layer 1, and the reinforcement layer 21 is formed in the above-mentioned manner, and is further plated and thickened to form the conductive layer 3.

[0046] The thickness of the conductive layer 3 can be selected according to suitability, and generally the thickness does not exceed 3 μm.

[0047] The positive electrode composite current collector based on the carbon-based conductive support layer can also increase the lateral thermal conductivity to a certain extent.

[0048] Embodiment 1

[0049] A commercially available 15μm*1.4m wide graphite film (paper) was selected, and a 1.2m wide PI film was selected to be laid flat on the surface of the graphite film as a carbon-based conductive support layer, and the temperature was raised to 900°C at 10°C / s, kept in a nitrogen atmosphere for 4h, and compacted at 20MPa;

[0050] Put the film on the machine for vapor deposition, preheat the carbonized layer, the temperature is about 700℃, the vehicle speed is controlled at 2m / s, the evaporation boat power is controlled (voltage 8-9v, current 600±80A, aluminum wire feeding 100mm / min, vapor deposition vehicle speed at 6m / s), evaporate aluminum to obtain a reinforcement layer, then reduce the vehicle speed to 4m / s, increase the wire feeding to 500mm / min, start vapor deposition, and obtain an aluminum layer about 1μm thick.

[0051] Embodiment 2

[0052] The difference from the first embodiment is that the formation of the carbonized layer is based on a coating method (20% polyacrylamide coating).

[0053] Embodiment 3

[0054] The difference from Example 1 is that the carbonization temperature is 1400° C. and the carbonization time is 2 h.

[0055] Comparative Example 1

[0056] A 1 μm aluminum layer is directly plated on the carbon-based conductive support layer, and the relevant plating process parameters are the same.

[0057] Comparative Example 2

[0058] The carbonized layer was prepared in the manner of Example 1 without coating the conductive layer.

[0059] Comparative Example 3

[0060] The carbonized layer was prepared in the manner of Example 3 without coating the conductive layer.

[0061] Adhesion test: A layer of Permacel P-94 double-sided adhesive is adhered to a 1mm thick aluminum foil, and the surface of the film to be tested is adhered to the double-sided adhesive, and a layer of ethylene acrylic acid copolymer film is covered on the film, and then hot-pressed at 1.3×105N / m2 and 120°C for 10s, cooled to room temperature, and cut into 150mm×15mm strips. Finally, the ethylene acrylic acid copolymer film of the sample strip is fixed to the upper fixture of the tensile machine, and the rest is fixed to the lower fixture. After fixing, the two are peeled at an angle of 180° and a speed of 100mm / min, and the maximum adhesion is recorded. At a sample preparation width of 15mm, the maximum adhesion values ​​of each comparative example and embodiment are shown in the following table.

[0062] Comparative Example 1 Comparative Example 2 Comparative Example 3 2.1N / 15mm 5.6N / 15mm 6.4N / 15mm Embodiment 1 Embodiment 2 Embodiment 3 3.3N / 15mm 3.9N / 15mm 4.0N / 15mm

[0063] It can be seen from the table that the carbonized layer obtained by the coating method and at a higher carbonization temperature has better bonding and anchoring effects with the carbon-based conductive support layer, ensuring the overall consistency of the subsequent film; in addition, the carbonized layer containing activated carbon particles formed by low-temperature carbonization can form compound crystals at a relatively mild plating temperature, increase the bonding strength between the aluminum molecules and the carbonized layer interface, and avoid overheating that causes decomposition of the bonded interface, thereby increasing the stability of the carbide and ensuring the bonding strength of the aluminum conductive layer.

[0064] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A positive electrode composite current collector, characterized in that: The invention comprises a carbon-based conductive support layer (1), a carbonized layer (2) formed on at least one surface of the carbon-based conductive support layer (1), the carbonized layer (2) containing activated carbon particles, the activated carbon particles forming a reinforcement layer (21) at the contact interface with vapor-deposited conductive layer particles, and the conductive layer particles deposit and thicken on the surface of the reinforcement layer (21) to form a conductive layer (3).

2. The positive electrode composite current collector according to claim 1, characterized in that: The carbon-based conductive support layer (1) is graphite, graphene or a mixed material thereof.

3. The positive electrode composite current collector according to claim 1, characterized in that: The thickness of the carbon-based conductive support layer (1) is 4-50 μm.

4. The positive electrode composite current collector according to claim 1, characterized in that: The carbonized layer (2) is formed by carbonizing a polymer film layer; the thickness of the carbonized layer (2) is 0.1-5 μm.

5. The positive electrode composite current collector according to claim 4, characterized in that: The polymer film layer is formed by a lamination or coating process.

6. The positive electrode composite current collector according to claim 1, characterized in that: The carbonization formation temperature of the carbonized layer (2) is 800-1500° C., and the heat preservation time is 1-4 hours.

7. The positive electrode composite current collector according to claim 1, characterized in that: The carbonization formation temperature of the carbonized layer (2) is between 1000°C and 1500°C.

8. The positive electrode composite current collector according to any one of claims 1 to 7, characterized in that: The interface temperature of the carbonized layer (2) in contact with the vapor-deposited conductive layer particles is set within the reaction temperature range of the activated carbon particles and the conductive layer particles to form a reinforcement layer (21).

9. The positive electrode composite current collector according to claim 8, characterized in that: The conductive layer (3) is made of aluminum, and the reaction temperature of its contact interface is between 1000° C. and 1300° C.

10. The positive electrode composite current collector according to claim 9, characterized in that: During plating, the surface temperature of the carbide layer (2) is 500-800°C, and the temperature of the evaporated aluminum vapor is 1100-1300°C.

Citation Information

Patent Citations

  • Preparation method of graphite-aluminum composite material

    CN111455323A

  • Current collector and lithium ion battery using same

    CN218525607U

  • Preparation method of carbon film aluminum mesh for current collector

    CN103545532A

  • Lithium battery with high specific energy and preparation method for current collector of lithium battery

    CN103545533A

  • Multi-layer structure lithium battery current collector, preparation method thereof and lithium battery

    CN112242527A